FT-Raman spectroscopic characterization of enamel surfaces irradiated with Nd:YAG and Er:YAG lasers - Sima Shahabi; Reza Fekrazad; Maryam Johari; Nasim Chiniforoush; Yashar Rezaei (Tabriz University of Medical Sciences, 2016)
Background. Despite recent advances in dental caries prevention, caries is common and remains a serious health problem. Laser irradiation is one of the most common methods in preventive measures in recent years. Raman spectroscopy technique is utilized to study the microcrystalline structure of dental enamel. In this study, FT-Raman spectroscopy was used to evaluate chemical changes in enamel structure irradiated with Nd:YAG and Er:YAG lasers. Methods. We used 15 freshly-extracted, non-carious, human molars that were treated as follows: No treatment was carried out in group A (control group); Group B was irradiated with Er:YAG laser for 10 seconds under air and water spray; and Group C was irradiated with Nd:YAG laser for 10 seconds under air and water spray. After treatment, the samples were analyzed by FT-Raman spectroscopy. Results. The carbonate content evaluation with regard to the integrated area under the curve (1065/960 cm-1) exhibited a significant reduction in its ratio in groups B and C. The organic content (2935/960 cm-1) area exhibited a significant decrease after laser irradiation in group B and C. Conclusion. The results showed that the mineral and organic matrices of enamel structure were affected by laser irradiation; therefore, it might be a suitable method for caries prevention.